2010
DOI: 10.1007/s10623-010-9416-6
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Harn–Lin’s cheating detection scheme

Abstract: Detection of cheating and identification of cheaters in threshold schemes has been well studied, and several solid solutions have been provided in the literature. This paper analyses Harn and Lin's recent work on cheating detection and identification of cheaters in Shamir's threshold scheme. We will show that, in a broad area, Harn-Lin's scheme fails to detect cheating and even if the cheating is detected cannot identify the cheaters. In particular, in a typical Shamir (t, n)-threshold scheme, where n = 2t − 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Because Shamir's scheme is a linear scheme, Harn‐Lin's scheme is also a linear scheme, which is secure against cheating from multiple cheaters. But later, the literature showed that this scheme can be broken by an easy attack.…”
Section: Previous Work On Cheating Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Shamir's scheme is a linear scheme, Harn‐Lin's scheme is also a linear scheme, which is secure against cheating from multiple cheaters. But later, the literature showed that this scheme can be broken by an easy attack.…”
Section: Previous Work On Cheating Detectionmentioning
confidence: 99%
“…The restriction of Harn‐Lin's scheme is that more than k players are required in secret reconstruction for cheating prevention. But later, the literature showed that this scheme can be broken by an easy attack. In , a linear secret sharing scheme with cheating detection for a general access structure was proposed, and it can be applied on ( k , n ) secret sharing schemes.…”
Section: Introductionmentioning
confidence: 99%
“…PBLS achieves the share size of |V | = | | / such that > 0 is the probability for successful cheating. Theorem 38 provides the security of PBLS and a proof on the share size of PBLS [30][31][32][33][34][35][36][37][38][39]. Theorem 38.…”
Section: Proposition 36 Let Be the Threshold Less Than Users Cannotmentioning
confidence: 99%
“…Liu et al 's scheme could be applied if system needs to share more than one secret [28]. Cramer et al 's scheme depends its security on the universal hash function, which means that it is not unconditionally secure, where Lin and Harn's scheme has been proved to be easily broken by a simple attack as pointed out by Ghodosi [30,31]. Liu et al 's scheme uses two polynomials to detect cheating during secret reconstruction and reduce the share size given to a user.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the approach of “majority voting” in our identification was first adopted in a cheating identification scheme where its practical applicability has been proved. Later, showed that the scheme can be broken by a flexible attack. The basic assumption in is that the attackers are malicious and they collude together to cheating.…”
Section: Proposed Verifiable Key Distribution Schemesmentioning
confidence: 99%